Mycobacterium avium subsp. paratuberculosis (Map) Fatty Acids Profile Is Strain-Dependent and Changes Upon Host Macrophages Infection - Alonso-Hearn, Marta; Abendaño, Naiara; Ruvira, Maria A.; Aznar, Rosa; Landin, Mariana; Juste, Ramon A. (Frontiers in Cellular and Infection Microbiology, 2017)
Johne´s disease is a chronic granulomatous enteritis of ruminants caused by the intracellular bacterium Mycobacterium avium subsp. paratuberculosis (Map). We previously demonstrated that Map isolates from sheep persisted within host macrophages in lower CFUs than cattle isolates after 7 days of infection. In the current study, we hypothesize that these phenotypic differences between Map isolates may be driven be the fatty acids (FAs) present on the phosphadidyl-1-myo-inositol mannosides of the Map cell wall that mediate recognition by the mannose receptors of host macrophages. FAs modifications may influence Map´s envelope fluidity ultimately affecting pathogenicity. To test this hypothesis, we investigated the responses of two Map isolates from cattle (K10 isolate) and sheep (2349/06-1) to the bovine and ovine macrophage environment by measuring the FAs content of extracellular and intracellular bacteria. For this purpose, macrophages cell lines of bovine (BOMAC) and ovine (MOCL-4) origin were infected with the two isolates of Map for 4 days at 37 °C. The relative FAs composition of the two isolates recovered from infected BOMAC and MOCL-4 cells was determined by gas chromatography and compared with that of extracellular bacteria and that of bacteria grown in Middlebrook 7H9 medium. Using this approach, we demonstrated that the FAs composition of extracellular and 7H9-grown bacteria was highly conserved within each Map isolate, and statistically different from that of intracellular bacteria. Analysis of FAs composition from extracellular bacteria enabled the distinction of the two Map strains based on the presence of the tuberculostearic acid (18:0 10Me) exclusively in the K10 strain of Map. In addition, significant differences in the content of Palmitic acid and cis-7 Palmitoleic acid between both isolates harvested from the extracellular environment were observed. Once the infection established itself in BOMAC and MOCL-4 cells, the FAs profiles of both Map isolates appeared relatively conserved. Our results suggest that the FAs composition of Map might influence its recognition by macrophages and influence the survival of the bacillus within host macrophages.